2020
DOI: 10.1055/a-1158-3151
|View full text |Cite
|
Sign up to set email alerts
|

Bewertung des Gesprächsverhaltens nach Schädel-Hirn-Trauma mit dem La Trobe Communication Questionnaire (LCQ): Erste Ergebnisse der deutschen Replikationsstudie an neurologisch gesunden Kontrollprobanden

Abstract: ZusammenfassungDer La Trobe Communication Questionnaire (LCQ) ist ein Verfahren, um Veränderungen des Gesprächsverhaltens nach Schädelhirntrauma zu erheben. Die vorliegende Version des LCQ ist im deutschsprachigen Raum derzeit der einzige psychometrisch untersuchte Fragebogen, mit dem kognitive Kommunikationsstörungen bei SHT sowohl aus der Perspektive von Betroffenen als auch Bezugspersonen bewertet werden können. Ziel der direkten Replikationsstudie war es zu prüfen, ob die deutsche Adaptation des LCQ zu ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Two exceptions to this are the MAKRO-Screening (Büttner, 2018) and the La Trobe Communication Questionnaire (LCQ; Douglas et al, 2000Douglas et al, , 2007a. Both use standardized procedures and for both, standard values of a healthy control group as well as evaluation studies (Büttner, 2014(Büttner, , 2016Büttner-Kunert et al, 2021b, 2022Royko and Büttner-Kunert, 2021) or replication studies (Büttner-Kunert et al, 2021a) are available.…”
Section: Assessing Discourse In Traumatic Brain Injury: Insights Into...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two exceptions to this are the MAKRO-Screening (Büttner, 2018) and the La Trobe Communication Questionnaire (LCQ; Douglas et al, 2000Douglas et al, , 2007a. Both use standardized procedures and for both, standard values of a healthy control group as well as evaluation studies (Büttner, 2014(Büttner, , 2016Büttner-Kunert et al, 2021b, 2022Royko and Büttner-Kunert, 2021) or replication studies (Büttner-Kunert et al, 2021a) are available.…”
Section: Assessing Discourse In Traumatic Brain Injury: Insights Into...mentioning
confidence: 99%
“…The LCQ is currently the only standardized questionnaire in German-speaking countries that can be used to assess sociocommunicative impairment and resources after TBI from the perspective of the affected person (self-assessment) and a close person (Büttner-Kunert et al, 2021b;Falkowska et al, 2021). In evaluation studies on the LCQ, neurologically healthy persons showed a significantly more critical self-assessment (LCQ-S) compared to the assessment of close others (LCQ-O), regardless of sex and educational level (Büttner-Kunert et al, 2021a). Studies on the use of the LCQ in IwTBI have shown that patients tend to rate themselves better than their relatives do (Douglas et al, 2000(Douglas et al, , 2007aDouglas, 2010b).…”
Section: Assessing Discourse In Traumatic Brain Injury: Insights Into...mentioning
confidence: 99%